Application of the Principles of Ecological Philosophy in Vietnam Social Development Today - Pham, Cong Nhat (H. : ĐHQGHN, 2019)
Climate change is now considered one of the most pressing “global issues” that humanity is addressing. In that context, there appear to be more and more sciences, including ecological philosophy, specifically studying ecological issues. Ecological philosophy, a new discipline of philosophy, dates back to the 1980s. Although it has recently emerged, ecological philosophy has proved to be a growing influence not only with its interdisciplinary nature, but also with its practicality and urgency. Based on the general theory of ecological philosophy and the recent results of ecological philosophy research in Vietnam, the article proposes a number of orientations and basic solutions for applying the results of ecological philosophy research in the current social development in Vietnam.